Evaluation of external and radiological landmark methods for optimizing ultrasound-guided right internal jugular venous catheterization depth in cardiac surgery - Artid Samerchua; Panuwat Lapisatepun; Pattaranee Srichairatanakool; Tanyong Pipanmekaporn; Wariya Sukhupragarn; Settapong Boonsri; Nutchanart Bunchungmongkol; Lalita Huntrakul (Scientific Reports)
Abstract The formula-based estimation of the right internal jugular venous (IJV) catheterization depth can be inaccurate when using ultrasound guidance. External landmark-based and radiological landmark-based methods have been proposed as alternatives to estimate the insertion depth. This study aimed to evaluate these methods using transesophageal echocardiography (TEE)-guided insertion depth as the reference. Ninety-seven adult cardiac surgery patients underwent real-time ultrasound-guided right IJV catheterization, with placement at the superior vena cava-right atrium (SVC-RA) junction under TEE guidance. The primary outcome compared the accuracy of external-landmark and radiological-landmark methods in estimating optimal catheter position (2 cm above to 1 cm below the SVC-RA junction), while secondary outcomes assessed their reliability and agreement with TEE. The external-landmark method proved more accurate than the radiological-landmark method (91.8% vs. 68%, p < 0.001) and had a higher correlation with TEE (r = 0.83 vs. 0.67). Bland–Altman analysis showed a mean difference of 0.08 cm between external-landmark and TEE methods (limits of agreement: -1.75 to 1.90 cm) and 0.43 cm for radiological-landmark (limits of agreement: -2.63 to 3.49 cm). Overall, the external-landmark method is a reliable and simple technique for estimating right IJV catheter depth and is more useful in cardiac surgery compared to the radiological-landmark method. Trial registration Thai Clinical Trials Registry (TCTR20200410012). Date registered April 9, 2020.